For the love of God and people a philosophy of Jewish law - Dorff, Elliot N. 1943-; Jewish Publication Society (Philadelphia, PA The Jewish Publication Society, 2007)
Bringing the topic down to earth -- The body of Jewish law : how Jewish law resembles other legal systems -- The covenantal soul of Jewish law : how Jewish law is unique -- Motivations to live by Jewish law -- Continuity and change in Jewish law -- The relationship of Jewish law to morality and theology -- Jewish law and custom -- Comparisons to the right and the left -- Applications of my theory of Jewish law to specific cases
Bringing the topic down to earth -- The body of Jewish law : how Jewish law resembles other legal systems -- The covenantal soul of Jewish law : how Jewish law is unique -- Motivations to live by Jewish law -- Continuity and change in Jewish law -- The relationship of Jewish law to morality and theology -- Jewish law and custom -- Comparisons to the right and the left -- Applications of my theory of Jewish law to specific cases
Includes bibliographical references and index
Keywords: Law, Semitic; Jewish Law -- Philosophy; Jewish Law -- Philosophy; Droit juif - Philosophie; Jewish law - Philosophy